Comment traiter les "soldats d'Hitler"? : la détention des prisonniers de guerre allemands au Canada, aux États-Unis et en Grande-Bretagne (1939-1945) : divergences et enjeux dans les relations interalliées - Turcotte, Jean-Michel (Université Laval, 2018)
This doctoral thesis explores the captivity of German prisoners of war in the hands of the three main Western Allies during the Second World War. More specifically, this work focuses on the relationships between the Canadian, British and American authorities regarding the treatment of some 600,000 “Hitler soldiers” held on their respective territories between 1940 and 1945. Such approach allows an international and transnational regard on war captivity. The relationship between the North Atlantic Allies according to captured enemy militaries indicates the political dynamics within the Alliance. Although each State applied its own detention measures and maintained its own diplomatic relation with the neutral organizations responsible for prisoners, in particular the International Committee of the Red Cross, as well as with Switzerland, the handling of these enemy soldiers was the object of a large inter-allied collaboration, while provoking important disagreement between the three holding powers. Contrary to the existing historiography, which often analyzes war detention in a national context, this thesis shows that the Allies established and developed war captivity as a transnational phenomenon. They corresponded with each other, contributed to their respective policies, participated in inter-allied projects, established common policies, met periodically for a better coordination of their actions and discussed their problems related to the detention of war, the solutions provided, and finally to share their positions on the Geneva Convention of 1929, the labour program, the denazification attempts and the repatriation of the captives by the end of 1945. The captivity of the German soldiers is thus the result of a mutual influence between the three North Atlantic Allies, resulting from the experiences of each Detaining Power. Following this approach, this study indicates that Canada, often considered a secondary power in historiography, played a determining role in the treatment of German prisoners. Through their ...